Doa Syafaat Untuk Sodom - Jusuf Haries Kelelufna (Jurnal Teologi dan Pelayanan Kerusso, 2021)
Several statements in the book of Genesis 18:16-33 raise theological problems, including the clause 'but Abraham still stands before God' and the concept of God's justice. The author wants to re-interpret the narrative of 'Abraham's intercession for Sodom' based on the continuity of the story and the theme of God's justice in the narrative. This research is an exegesis of the biblical text carried out by reading the text research tool (Apparatus Critticus), analyzing Hebrew grammar and lexicons. The results of the analysis are then linked to the believers' current prayers as their relevance. The results of the analysis show that the phrase 'but Abraham still stands before God' should be translated as 'but God is still standing before Abraham' by placing God as the subject which means God who prays, serves, becomes the initiator and as a just judge. Abstrak Indonesia Beberapa pernyataan dalam kitab Kejadian 18: 16-33 mengangkat masalah teologis, termasuk klausa 'tetapi Abraham tetap berdiri di hadapan Tuhan' dan konsep keadilan Tuhan. Penulis ingin menafsirkan kembali narasi 'Abraham syafaat untuk Sodom' berdasarkan kesinambungan cerita dan tema keadilan Tuhan dalam narasinya. Penelitian ini merupakan eksegesis teks alkitabiah yang dilakukan dengan membaca alat penelitian teks (Apparatus Critticus), menganalisis tata bahasa dan leksikon Ibrani. Hasil analisis kemudian dikaitkan dengan doa-doa orang percaya saat ini sebagai relevansinya. Hasil analisis menunjukkan bahwa kalimat 'tetapi Abraham masih berdiri dihadapan Tuhan' harus diterjemahkan sebagai 'tetapi Tuhan tetap berdiri dihadapan Abraham' dengan menempatkan Tuhan sebagai subjek yang berarti Tuhan yang berdoa,